Improved Engine Performance Using Ozone Generator - Anantama, Herlang; Achmad Fuad, Erika; Waluyo, Budi; Saifudin, Saifudin (Borobudur Engineering Review, 2023)
An increase in the number of vehicles today will result in an increase in fuel oil consumption and emission pollution. Therefore, it is necessary to optimize for fuel oil economy and emission reduction by improving engine performance. Improving engine performance can be done through several factors, including; with compression ratio, volumetric efficiency and fuel quality. The purpose of this study is to prove that with the addition of ozone (O3) the combustion process will be more reactive than oxygen (O2) so that it can produce faster and more complete combustion, This study will convert oxygen (O2) into more reactive ozone (O3) by using a 15 g/h plasma plasma generator ozone installed on an air filter. Engine performance testing includes engine power and torque using a 50L super dyno type dynamometer chassis. The test results showed, with ozone generator engine torque increased from 0 – 0.5 Nm and increased engine power from 0 – 0.4 KW compared to without using an ozone generator. Nevertheless, the use of ozone (O3) at a high equivalent ratio can lead to knocking